Variations in leisure activity preferences based on ethnicity of urban park users / Amelia Ahmad - Ahmad, Amelia (2015)
Urban parks provide excellent setting for urbanites to pursue leisure time activities. In an ethnically diverse country as Malaysia, park designers, planners and managers are presented with challenges to ensure the promotion of equal access as well as to meet the needs and expectations of the different ethnic groups. Many urban parks failed to incorporate the socio-cultural and behavioural characteristics of the varied park users, focusing mainly on the material and physical aspects of their designs. The concern for ethnic variations in leisure activity preferences occurs due to the fact that the recreation behaviours of some groups may have caused them to be marginalised in their recreation experiences, or lead to facility damage and resource degradation, and also little is known on how ethnic background of recreational users shaped their recreational experiences. This research aims to examine the variations in leisure activity preferences of urban park users across three main groups, that is, Malays,Chinese and Indians. The leisure activity preferences examined includes park usage patterns and participation; social composition; and settings. Two urban parks located in Perak were studied, both being, Taiping Lake Garden (TLG) and Padang Polo, Ipoh (PPI). The data for this study was collected using two methods, that is, observation and survey; and data were then analysed using descriptive statistics. Findings revealed differences and similarities related to leisure activity preferences of the three ethnic groups. Chinese park users were found to be the most enthusiastic users as compared to Malays and Indians. Physical exercising, such as walking, was preferred by most parks users. Majority of the park users preferred companion, especially of their same ethnic groups, when frequenting the parks. Different groups also have different setting preferences. Factors such as time availability, cultural values, park’s physical characteristics, experiences sought and safety aspect, were identified to have contributed to the variations in leisure activity preferences. These findings contributed to a better understanding of the recreation style and leisure preferences of the culturally and ethnically diverse user groups. The findings will assist park designers, planners and managers to improve and enhance on the design, planning and management of urban parks. These can be achieved through better park designs, planned park activities and programmes, as well as, maintenance and clear management policies and strategies of the parks which will meet future park user’s needs and expectations